2012
DOI: 10.1186/1297-9716-43-76
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant and immunostimulatory effects of a D-galactose-binding lectin from Synadenium carinatum latex (ScLL) in the mouse model of vaccination against neosporosis

Abstract: Vaccination is an important control measure for neosporosis that is caused by a coccidian parasite, Neospora caninum, leading to abortion and reproductive disorders in cattle and serious economic impacts worldwide. A D-galactose-binding lectin from Synadenium carinatum latex (ScLL) was recently described by our group with potential immunostimulatory and adjuvant effects in the leishmaniasis model. In this study, we evaluated the adjuvant effect of ScLL in immunization of mice against neosporosis. First, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 42 publications
0
24
0
8
Order By: Relevance
“…Previous in vitro and in vivo studies showed ScLL and ArtinM can be safely administered on murine models (Panunto-Castelo et al, 2001; Afonso-Cardoso et al, 2007; Cardoso et al, 2012). Furthermore, in vivo models demonstrated that ScLL presents no cytotoxic activity against J774 cells or peritoneal murine macrophages (Souza et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous in vitro and in vivo studies showed ScLL and ArtinM can be safely administered on murine models (Panunto-Castelo et al, 2001; Afonso-Cardoso et al, 2007; Cardoso et al, 2012). Furthermore, in vivo models demonstrated that ScLL presents no cytotoxic activity against J774 cells or peritoneal murine macrophages (Souza et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the possibility to occur parasite drug resistance is an additional drawback to treat this disease based only on chemotherapy (Hui et al, 2015). Due the immunostimulatory effect of plant lectins, studies have been developed to implement of vaccination protocols using new agents to stimulate the immune system, as ScLL and ArtinM lectins extracted from plants (Cardoso et al, 2011, 2012; Souza et al, 2013). However, there is no previous study analyzing the therapeutic use of ScLL and ArtinM against T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Despite its anti-inflammatory activity, 13,15,16 ScLL has not been evaluated in the oral cavity until the present time. The purpose of the present study was to investigate the effect of ScLL, stimulated with Porphyromonas gingivalis lipopolysaccharides (LPS), on the viability, proliferation and release of IL-10 in gingival fibroblasts.…”
Section: Introductionmentioning
confidence: 99%